EXPLORATION OF EFFECTIVE HIGHER EDUCATION LEADERSHIP PRACTICES IN CULTIVATING STUDENT CHARACTER IN ALIGNMENT WITH ISLAMIC PRINCIPLES - Yuarini Wahyu Pertiwi; Pandu Perdana Putra; St. Rahmah; Najamuddin Petta Solong (Indonesian Journal of Education (INJOE), 2023)
This study examined effective practices in higher education leadership for shaping students' character within an Islamic framework. Drawing from moral and ethical development theory, virtue ethics, and positive psychology, it explored the intricate relationship between leadership, character development, and Islamic principles. Through an in-depth analysis of character development initiatives in Islamic-focused higher education institutions, the study identified vital strategies: curriculum integration, faculty training, assessment, community engagement, cultural competency, and holistic support services. Additionally, it emphasized the importance of promoting critical thinking and reflection to help students evaluate their values against Islamic principles. Leadership theories like transformational, servant, and ethical leadership were highlighted to guide leaders to align with Islamic values such as justice, trustworthiness, and consultation. Case studies of the successful integration of Islamic guidance into leadership approaches offered insights for other institutions. Nonetheless, the study recognized existing research gaps and the need for further exploration of leadership practices and the long-term impact of character development initiatives.